Syntheses of novel N-confused porphyrins bearing amino and carboxylic acid functional groups - Dela Rosa, Mira Anne C.; Arco, Susan D. (Quezon City Institute of Chemistry, College of Science, University of the Philippines Diliman, In Collaboration with the Institute of Chemistry Academia Sinica Nankang, Taipei, Taiwan, 2010)
Iron (II) complexes of N-confused tetraphenylporphyrin (NCTPP) have been reported to react with S-nitrosothiols forming an iron nitrosyl complex with the sulfur atom inserted in the Fe-C bond. Hence the possibility of using NCTPP as a probe for S-nitrosylation in proteins has become apparent. However, NCTPP is poorly soluble in biological medium such that the derivatization of NCTPP to include a site for attachment of water soluble nanoparticles is being explored. In line with this, NCTPP is being derivatized with amino and carboxylic acid functional groups and in this work, substituted N-confused porphyrins bearing amino or carboxylic acid groups were synthesized.
Thesis (M.S. Chemistry)--University of the Philippines Diliman
Keywords: Porphyrins; Carboxylic acids